Garis Ideologi Agraria Di Era Presiden Joko Widodo - Yanto, Hery (Universitas Sriwijaya, 2022)
The inauguration of President Jokowi for a second term has made the public hope that there will be a significant breakthrough in the agrarian sector. However, this hope has been disappointed—again by Jokowi—because of the passage of the UU Cipta Kerja which has a significant impact on agrarian issues. Civil groups noted that the law will further add to the blurry future of agrarian reform as enshrined in the fifth precepts of Pancasila and Article 33 of the UUD 1945. Taking this background, the author is interested in analyzing the lines of agrarian ideology in the era of President Joko Widodo, using qualitative methods that based on literature studies, and using the analysis knife of the Fifth Precepts of Pancasila and Article 33 of the UUD 1945 to provide a deeper perspective on agrarian policy in the era of President Jokowi's leadership.